The Rich and the Great Recession - Bakker, Bas (IMF Working Papers; Working Paper ;, 2014)
Most papers explaining the macro causes of the U.S. Great Recession focus on the behavior of the middle class: how its saving rate declined in the pre-crisis years, then surged following the crisis. This paper argues that the saving rate of the rich followed a similar pattern, the result of wealth effects associated with a boom-bust in asset prices. Indeed, the swings in saving by the rich must actually have played the most important role in the consumption boom-bust, since since the top 10 percent account for almost half of income and two-thirds of wealth. In other words, the rich played a critical role in the Great Recession.